An Unusual Mass of the Neck: Primary Hydatid Cyst - Bakır, Salih; Gun, Ramazan; Fırat, Ugur; Yorgancılar, Ediz; Tekbas, Guven; Topcu, İsmail (Fırat University, 2011)
Hydatid disease is a common parasitic infestation caused by the parasite Echinococcus granulosus. It is a serious health problem most frequently encountered in rural areas where domestic livestock-raising is common. Complete surgical excision is the gold standard treatment for hydatid cyst. Postoperative medical treatment with antihelminthic drugs (benzimidazole derivatives) are frequently combined with surgical treatment to prevent recurrence of disease and high-risk contamination. Although hydatid cysts usually involve in liver and lungs, less frequently may occur in any area of the body. A hydatid cyst occurrence in the head and neck area is extremely rare. So this disease does not usually come to mind. Therefore in this case, we wish to draw attention to possibility of the hydatid disease in the neck. For this reason, we present an unusual case of primary hydatid cyst located in the neck region in a 50-year-old male patient.

Hidatik kist hastalığı, Echinococcus granulosus adlı tenyanın larvalarının neden olduğu parazitik bir enfestasyondur. Büyük ve küçükbaş hayvan yetiştiriciliğinin yaygın olduğu kırsal kesimlerde ve köpek besleme alışkanlığının bulunduğu insan topluluklarında sık görülür. Hidatik kistin tedavi-sinde cerrahi “altın standart” olarak kabul edilmektedir. Benzimidazol türevleri cerrahi yapılamayacak olgularda ya da cerrahi sonrası rekürrensleri önlemek için kullanılır. Kist hidatik genellikle karaciğer ve akciğerde görülmekle beraber, vücudun herhangi bir bölgesinde oluşabilir. Baş ve boyun bölgesinde kist hidatik oluşumu son derece nadirdir. Bu yüzden boyunda kitle ile gelen hastada bu hastalık genellikle ayırıcı tanıda akla gelmez. Bu nedenle bu olgu sunumunda, 50 yaşındaki bir erkek hastanın primer kist hidatik tanısı almış boyun bölgesindeki nadir kistik kitleyi sunarak, boyunda hidatik kist hastalığı olasılığına dikkat çekmek istedik.
Nadir Bir Boyun Kitlesi: Primer Hidatik Kist